Antigen-driven focal inflammatory death of malaria liver stages - Bayarsaikhan, Ganchimeg; Akbari, Masoud; Yui, Katsuyuki; Amino, Rogerio (Frontiers in Microbiology, 2015)
Multiple immunizations using live irradiated sporozoites, the infectious plasmodial stage delivered into the host skin during a mosquito bite, can elicit sterile immunity to malaria. CD8+ T cells seem to play an essential role in this protective immunity, since their depletion consistently abolishes sterilizing protection in several experimental models. So far, only a few parasite antigens are known to induce CD8+ T cell-dependent protection, but none of them can reach the levels of protection afforded by live attenuated parasites. Systematic attempts to identify novel antigens associated with this efficient cellular protection were so far unsuccessful. In addition, the precise mechanisms involved in the recognition and elimination of parasitized hepatocytes in vivo by CD8+ T cells still remain obscure. Recently, it has been shown that specific effector CD8+ T cells, after recognition of parasitized hepatocytes, recruit specific and non-specific activated CD8+ T cells to the site of infection, resulting in the formation of cellular clusters around and in the further elimination of intracellular parasites. The significance of this finding is discussed in the perspective of a general mechanism of antigen-dependent focalized inflammation and its consequences for the elimination of malaria liver stages.